If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -7(y + 2) = 9 + -3y Reorder the terms: 2 + -7(2 + y) = 9 + -3y 2 + (2 * -7 + y * -7) = 9 + -3y 2 + (-14 + -7y) = 9 + -3y Combine like terms: 2 + -14 = -12 -12 + -7y = 9 + -3y Solving -12 + -7y = 9 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. -12 + -7y + 3y = 9 + -3y + 3y Combine like terms: -7y + 3y = -4y -12 + -4y = 9 + -3y + 3y Combine like terms: -3y + 3y = 0 -12 + -4y = 9 + 0 -12 + -4y = 9 Add '12' to each side of the equation. -12 + 12 + -4y = 9 + 12 Combine like terms: -12 + 12 = 0 0 + -4y = 9 + 12 -4y = 9 + 12 Combine like terms: 9 + 12 = 21 -4y = 21 Divide each side by '-4'. y = -5.25 Simplifying y = -5.25
| -7[5+3(6+9)]= | | (6y^3-y^2+4)(4y^2+y+1)= | | -7x+7+5x=-3x+12 | | 8.5p=7.5p | | -7x+4+5x=-3x+9 | | 0.2(x+1)=0.3(x+11) | | -6(x+1)+2(7x+9)= | | 2x+149=9x-5 | | 9-4(y+7)=7+3y | | x^4+9x^2+400=0 | | 3b-2=19 | | 2x-3+5x=4+4x+1 | | 2x+y-2z=2 | | s^2+9s+81=0 | | 7*6= | | 89-7x=29x+21 | | X^3=81x | | x-4y+2z=-11 | | 26=7x+x+2 | | 30-5a=10 | | -.5(y+5)=-1 | | c/8+10=15 | | 3x+2y-4z=3 | | c/8=15 | | 12x^2+12x-24=0 | | 12-10x=62-24x | | -7(x+1)=2x-34 | | 24a-22=-4(1-6n) | | -x+3=-3x+11 | | 4x^2-48+44=0 | | x^2+36x=144 | | 6x-3=2x+5 |